PEMBUATAN DAN KUALITAS ARANG AKTIF DARI KAYU SENGON (Paraserianthes falcataria) SEBAGAI BAHAN ADSORBEN - Gustan Pari; Buchari Buchari; Aminudin Sulaeman (Jurnal Penelitian Hasil Hutan, 1996)
The characterization  of activated charcoal from  steam activation of sengon (Paraserianthes falcataria) wood is reported in this paper. The purpose of this investigation was to study  the influences  of  temperature  and  concentration  of chemical  activator  on the activated  charcoal yield  and its  quality. The activated  charcoal  was produced  in  a stainless steel  retort  with electrical  heater  at the temperature  of  7000C, 8000C  and  9000C  and  for  activation  used NH4HCO3 with its consentration  0,5; 1,0; 3,0; 5,0 and 10% respectively.The best quality of the activated charcoal produced when the activation temperature  was 9000C with the NH4HCO3 1,0 %. The yield  of  activated  charcoal  was  5,90%,  moisturecontent 6,39  %, ash content 9,15 %, volatile matter 8,81 %, fixed  carbon 82,04 %. Adsorptive capacity of iodine was 1154,4  mg/g, NH3 25,08 %, CHCl3 42,28 %, CCl4 51,74 %, benzene 49,10% and methylene  blue 138,80 - 319,00  mg/g. Surface area was 1143,7 m2/g. The most abundance  of particle  size  was 4,00 - 5,65 micron  and pore volume  16,00 - 22,62  micron. High and diameter pore was 37,49 and 22,52 micron.